The ultraviolet spectroscopic evolution of the low-luminosity tidal disruption event iPTF16fnl. Issue 1 (22nd September 2017) - Brown, J. S.; Kochanek, C. S.; Holoien, T. W.-S.; Stanek, K. Z.; Auchettl, K.; Shappee, B. J.; Prieto, J. L.; Morrell, N.; Falco, E.; Strader, J.; Chomiuk, L.; Post, R.; et al.
Abstract: We present the ultraviolet (UV) spectroscopic evolution of a tidal disruption event (TDE) for the first time. After the discovery of the nearby TDE iPTF16fnl, we obtained a series of observations with the Space Telescope Imaging Spectrograph (STIS) onboard the Hubble Space Telescope ( HST ). The dominant emission features closely resemble those seen in the UV spectra of the TDE ASASSN-14li and are also similar to those of N-rich quasars. There is evolution in the shape and central wavelength of the dominant emission features over the course of our observations, such that at early times the lines tend to be broad and redshifted, while at later times they are narrower and peak near the wavelengths of their atomic transitions. Like ASASSN-14li, but unlike N-rich quasars, iPTF16fnl shows neither Mg ii 2798 Å nor C iii ] 1909 Å emission features. We also present optical photometry and spectroscopy, which suggest that the complex He ii profiles observed in the optical spectra of many TDEs are in part due to the presence of N iii and C iii Wolf–Rayet features, which can potentially serve as probes of the far-UV when space-based observations are not possible. Finally, we use Swift X-ray Telescope and Ultraviolet/Optical Telescope (UVOT) observations to place strong limits on the X-ray emission and determine the characteristic temperature, radius and luminosity of the emitting material. We find that iPTF16fnl is subluminous and evolves more rapidly than other optically discovered TDEs.